Low-Temperature Performance and Durability of Electric Vehicle Battery Cells Under Isothermal Conditions - Steven Recoskie; Dean D. MacNeil; Ken Darcovich; Joel Perron; Samuel Pedroso (Energies)
Electric vehicle (xEV) battery durability significantly impacts the long-term operation, consumer satisfaction, and market adoption of xEVs. As driving range diminishes over time, it affects vehicle service life and lifecycle GHG emissions. Measuring the full service life of xEV batteries in laboratory tests presents technical and logistical challenges, necessitating representative measurements for parameterizing numerical models. These models are crucial for predicting long-term performance and rely on high-quality experimental data. While performance and aging trends under extreme temperatures are documented, cell thermal contact conditions suitable for direct model input are not well characterized. This study investigates lithium-ion cells from three xEV types, cycled at constant currents from C/40 to 1C, at temperatures between −15 °C and +45 °C, over 1000 cycles in a multi-year campaign. Stable isothermal cell temperatures were achieved using custom-built liquid immersion baths with forced convection, highlighting fundamental electrochemical behaviors by decoupling complex self-heating not typically monitored in air environments. The data inform and validate physics-based models on temperature-dependent performance and durability, providing operational limits to enhance cell and battery thermal management design and educate xEV consumers about conditions affecting performance, range, and durability.